Management of Osmoprotectant Uptake Hierarchy in Bacillus subtilis via a SigB-Dependent Antisense RNA - Rath, Hermann; Reder, Alexander; Hoffmann, Tamara; Hammer, Elke; Seubert, Andreas; Bremer, Erhard; Völker, Uwe; Mäder, Ulrike (Frontiers in Microbiology, 2020)
Under hyperosmotic conditions, bacteria accumulate compatible solutes through synthesis or import. Bacillus subtilis imports a large set of osmostress protectants via five osmotically controlled transport systems (OpuA to OpuE). Biosynthesis of the particularly effective osmoprotectant glycine betaine requires the exogenous supply of choline. While OpuB is rather specific for choline, OpuC imports a broad spectrum of compatible solutes, including choline and glycine betaine. One previously mapped antisense RNA of B. subtilis, S1290, exhibits strong and transient expression in response to a suddenly imposed salt stress. It covers the coding region of the opuB operon and is expressed from a strictly SigB-dependent promoter. By inactivation of this promoter and analysis of opuB and opuC transcript levels, we discovered a time-delayed osmotic induction of opuB that crucially depends on the S1290 antisense RNA and on the degree of the imposed osmotic stress. When these data are viewed in an ecophysiological framework, it appears that during the early adjustment phase of B. subtilis to acute osmotic stress, the cell prefers to initially rely on the transport activity of the promiscuous OpuC system and only subsequently fully induces opuB. Our data also reveal an integration of osmostress-specific adjustment systems with the SigB-controlled general stress response at a deeper level than previously appreciated.